Fungi and their medicinal properties: a scientometric study (Acta Scientiarum. Biological Sciences, 2023)
Fungi are eukaryotic, heterotrophic, unicellular or multicellular organisms that feed by absorption. Some of their attributes stand out in the medicinal and pharmaceutical sector since several genera of fungi have metabolic properties and compounds related to the manufacture of numerous medicines. In this context, the objective of this study was to carry out a scientometric analysis to verify the application and properties of medicinal fungi as well as their contributions to the knowledge of medicinal fungi. A survey of applied literature, which included the word “Medicinal fungi”, was carried out based on the articles indexed in the Thomson Reuters base (www.isiwebofknowledge.com), considering the period from 2003 to 2021. One hundred and thirty-nine scientific articles were used for the scientometric analysis, and these were divided into six time intervals (2003-2006, 2007-2009, 2010-2012, 2013-2015, 2016-2018, 2019-2021). An increase was noted in the scientific production on medicinal fungi from 2007 onwards, mostly presenting publications with an experimental approach. The phylum Basidiomycota, followed by Ascomycota, presented the highest number of records in the study, mainly with applications aimed at antitumor and antibacterial activity. Therefore, the importance of studies that aim to expand the knowledge of the properties of medicinal fungi is highlighted, providing effective results for various diseases, since their cultivation and development can positively generate equitable economic growth, with regional and national impacts.